Pengimplementasian Program H.E.E.C Atau Health, Environment, And Educational Community Untuk Mencegah Resiko Penyakit Stunting Di Desa Depok, Kecamatan Kalibawang, Kabupaten Wonosobo - Siti Zulfah; Saifu Rohman; Sefilia Sari; Zahrotun Nafisa Arifah; Almas Isabella Paramitha; Mar Atus Solihah; Windarti Windarti; Umi Kulsum; Sri Susanti; Muawanah Muawanah; Ahmad Kholisun (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2022)
Stunting, as a condition of lack of nutrition in children which is characterized by impaired child growth, is a crucial problem in Indonesia. With the high number of cases of malnutrition in children, there is required a collaborative and integrated contribution between academics and the community. Therefore, in an effort to prevent the emergence of stunting cases in Depok village, Kalibawang district, Wonosobo regency, this research was conducted with the main objective of broadening public knowledge and awareness of the risk of stunting through the application of HEEC program. HEEC or Health, Environment and Educational Community, is a program formed from a combination of the TOGA counseling and planting program and the English class Language Forum program. With a qualitative approach, the method used in this research is CBR or Community-Based Research. In collecting the research data, the researchers used observation and interview as data collection techniques. Based on the research that has been done, the HEEC program has been implemented well and has made a major contribution to stunting prevention efforts. This can be analyzed from the results of observation and interview where the community is helped in terms of enriching their knowledge and awareness of the importance of maintaining physical health in order to avoid the risk of stunting and in preparing the next generation with broad insights who can improve the welfare of rural communities. Keywords: stunting, HEEC program, Language Forum, TOGA counseling and planting program